The comprehension of metaphorical expressions in academic texts by Iraqi EFL learners - Al-Mashhadani, Omar Ahmed Badr; Ravichandran Vengadasamy, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Metaphor is so pervasive in language use that we hardly come across a language situation that does not utilise metaphors. Previous studies revealed that EFL learners face certain difficulties in identifying and understanding metaphors in English comprehension texts in the academic setting. Since the true nature and magnitude of this problem have not been studied thoroughly yet among Iraqi EFL learners, this paper aims to find out their ability to comprehend metaphors in academic reading. The analysis is based on Lakoff and Johnson’s (1980) Conceptual Metaphor Theory. The researcher conducted several reading sessions for 30 Iraqi EFL university learners to collect data for the study. The reading sessions included the use of six comprehension texts, selected from the learners’ textbook specified for the reading comprehension class. Through the use of a questionnaire, students were required to explain how they selected and understood metaphors. The participants’ responses were varied; therefore, they were schemed into four categories: successful understanding, misunderstanding, non-understanding, and literal understanding. The findings revealed that students who understood metaphorical (successful understanding) expressions scored the highest percentage followed by misunderstanding, non-understanding, and literal understanding respectively. The findings also showed that there are social, cultural, linguistic and semantic factors, as well as personal views, that influence the metaphor identification and comprehension abilities among the subjects.